2019
DOI: 10.1021/acsnano.9b01292
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystals in Molten Salts and Ionic Liquids: Experimental Observation of Ionic Correlations Extending beyond the Debye Length

Abstract: The nature of the interface between the solute and the solvent in a colloidal solution has attracted attention for a long time. For example, the surface of colloidal nanocrystals (NCs) is specially designed to impart colloidal stability in a variety of polar and nonpolar solvents. This work focuses on a special type of colloids where the solvent is a molten inorganic salt or organic ionic liquid. The stability of such colloids is hard to rationalize because solvents with high density of mobile charges efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 70 publications
(115 reference statements)
5
78
0
Order By: Relevance
“…Only one group provided an overall picture about colloidal stability, however, mainly in molten salts. 13,14 Ueno et al 15 studied the stability of hydrophilic silica particles in 11 ionic liquids, which produced some well dispersed systems according to rheological measurements. The stability was attributed to specic interactions between the surface-bound OH and one of the ions of the ionic liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Only one group provided an overall picture about colloidal stability, however, mainly in molten salts. 13,14 Ueno et al 15 studied the stability of hydrophilic silica particles in 11 ionic liquids, which produced some well dispersed systems according to rheological measurements. The stability was attributed to specic interactions between the surface-bound OH and one of the ions of the ionic liquid.…”
Section: Introductionmentioning
confidence: 99%
“…These values further lead to the number of IL-component pairs trapped by the single NP on its surface to be 200, 340 and 1900, respectively, (Tables S2-4). The solvation layer thicknesses estimated are also roughly translated to single, 1-2 and 4-5 ion-pair layers, respectively, which are apparently smaller compared to those measured by the surface force measurements on a flat surface [15][16][17] but in a similar range to that estimated based on the PDF analysis for NPs in an ionic liquid [14]. The surface force measurement is possible to induce a confinement effect, which enhances the ordering of ionic components confined between two surfaces [16,17].…”
Section: Resultsmentioning
confidence: 62%
“…However, no apparent peak corresponding to regular lamellar structure appears and three peaks characteristic to P 18 Tf 2 N are still prominent. It is therefore concluded that the IL components gave a limited change from the bulk microstructure to make a solvation layer on the NPs, which could be evaluated as the enhancement of ion-ion correlations by the careful PDF analysis [14]. The orientation of pyrrolidinium cations should change on the NPs but the interionic interactions and van der Waals forces between alkyl chains operate in the solvation layer in a similar range to the bulk phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding nanoparticles (NPs) to ionic liquids can further improve the systems properties. 6 The addition of charged nanoparticles, for example, can improve the thermoelectric properties compared to mentally determined by the same group using X-ray pair distribution analysis on nanoparticles in molten salts 14 . This layering at the interface was invoked to explain colloidal stability for three types of nanoparticle surfaces: bare (i.e.…”
Section: Introductionmentioning
confidence: 99%